"Racing" to the IBOR transition finish line. Issue 4 (23rd September 2021) - Forrester, J. Paul; Miller, Mary Jo N.
Abstract : Purpose: Summarize and review the key developments during the first three-quarters of 2021 relating to transition of the London InterBank Offered Rate (LIBOR) to alternative risk-free rates, in accordance with the guidance of global regulators and market participants. Design/methodology/approach: Outlines and explains four key events to date during 2021 that are instrumental to the success of LIBOR transition, including the ISDA 2020 IBOR Protocol and Supplement, the 5 March 2021 announcements by ICE Benchmark Administration and the Financial Conduct Authority, the transition of interdealer swap conventions from LIBOR to SOFR, and the ARRC endorsement of the CME Group SOFR term rate. Findings: The global adherence to the ISDA Protocol and Supplement, the successful launch of "SOFR First" and other "RFR First" swaps convention transitions, and the ARRC's endorsement of CME's SOFR term rate have given the market the clarity and tools that it needs to complete the transition away from LIBOR by the deadlines fixed by the 5 March 2021 benchmark transition event. Practical implications: It now is clear that market participants globally have the resources to, and must, move to adopt alternative reference rates and related operational systems and other infrastructure to cease origination of new LIBOR-linked contracts after 31 December 2021. The ARRC's endorsement of the SOFR term rate for business loans and related derivatives and securitizations is a critical positive development for the structured finance market. Originality/value: Expert analysis and guidance from experienced finance lawyers.